Soil Carbon Sequestration in Agroecosystems of India - Lal, Rattan (Journal of the Indian Society of Soil Science, 2015)
Soils of agroecosystems of India are degraded, depleted and severely devoid of the soil organic carbon (SOC) pool which is often <1 g kg-1 or barely 10 to 15 Mg C ha-1 to 40 cm depth. Thus, crop yields are low, water and air resources are polluted, and the overall environment is degraded. Indeed, environmental sustainability in India remains a major issue to be addressed. Concentration of SOC is a strong determinant of soil quality. Furthermore, quality of soil also impacts those of plants and animals, and thus, health of human population. Restoration of SOC pool to above the threshold level of 10 to 15 g kg-1 in the root zone is essential to advancing food and nutritional security, achieving climate change adaptation and mitigation, improving water quality and renewability, increasing biodiversity, and alleviating poverty by increasing productivity. Among causes of the severe depletion of SOC pool are extractive farming practices of residue removal, indiscriminate plowing, excessive irrigation by flooding, none or unbalanced application of fertilizers, and use of dung as a household fuel rather than manure. Uncontrolled grazing and shifting cultivation also contribute to soil degradation. The extent and severity of degradation are exacerbated by accelerated erosion by water and wind, salinization, acidification, elemental imbalance, and anerobiosis. Thus, soil degradation trends must be reversed by improving SOC concentration through creation of a positive soil/ecosystem C budget. Among best management practices (BMPs) are afforestation and reforestation of hill slopes and agriculturally marginal lands. Establishment of plantations and agroforestry systems is another option. Some BMPs for cropland, essential to improving SOC pool and advancing food security, are conservation agriculture, integrated nutrient management, and crop diversification especially of the rice-wheat system in the Indo-Gangetic Plains. Policy interventions are needed to promote the adoption of BMPs through payments for ecosystems services. Improved governance and strong political will power are essential to revolutionizing the stagnating Indian agriculture.